An Intertemporal Equilibrium Beta Pricing Model - Connor, Gregory; Korajczyk, Robert A. (Review of Financial Studies, 1989)
[This article develops an intertemporal, discrete-time, competitive equilibrium version of the arbitrage pricing theory (APT) and explores the econometric implications of this model under various restrictions on investor preferences and on the dynamic behavior of dividends. We describe conditions under which the econometric techniques typically used for estimating and testing the APT can be shown to be consistent with our economic model. We relate our intertemporal version of the APT to the static APT and to Merton's intertemporal capital asset pricing model.]